Current knowledge about interactions between avian dendritic cells and poultry pathogens. (March 2020) - Zmrhal, Vladimir; Slama, Petr
Abstract: In poultry production conditions today, birds are surrounded by viral, bacterial, and parasitic agents. DCs are the main antigen-presenting cells located in tissues of the body, and their role involves recognizing antigen structures, engulfing and processing them, and subsequently presenting antigen peptides on their surface by major histocompatibility complex, where T cells and B cells are stimulated and can begin appropriate cellular and antibody immune response. This unique function indicates that these cells can be used in producing vaccines, but first it is necessary to culture DCs in vitro to identify the principles of their interactions with pathogens. The following review summarizes our current knowledge about avian dendritic cells and their interactions with pathogens. It provides a basis for future studies of these unique cells and their use in vaccine development. Highlights: Sources of dendritic cells for in vitro experiments. Effect of viral diseases on chicken dendritic cells. Effect of parasitic diseases on chicken dendritic cells. Effect of bacterial diseases on chicken dendritic cells. Novel methods in antigen delivery to dendritic cells.